Javanese Cultural Keywords from the Sambatan Ritual Discourse: An Ethno-pragmatic Perspective - Pratiwy, Devi; Asnani, Asnani; Wulan, Sri; Fauzi, Mohd; Pardi, Pardi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study aims to reveal cultural keywords from a particular cultural tradition, sambatan held by the Javanese-speaking community in Tanjung Harapan Village, Air Putih District.  Historically, the Javanese-speaking community in the area were migrants from their ancestral lands on the island of Java.  This traditional activity refers to the communal activity of preparing and building houses, between the owner and the local community. Investigation of the cultural norms can be seen from the use of grammar aspect, lexicon, and linguistic routines of a language. Those were directly related to the context of the situation (context-bound), which determined the way society speaks. The objective of this research is to explore the cultural key word entities in the discourse. Following the ethno-pragmatic perspective, the parameter of cultural discourse is the core meaning of the language used. It gives rise to variations in speech forms as the embodiment of the cultural values of each ethnic group, which in turn creates different configurations for language used. This study was designed using a synchronic-ethnographic field study. In conducting the research, the phenomenological approach was adopted. Data were obtained by following the participating observation method and in-depth interviews. The data analysis followed the ethno-pragmatic methodological tools; semantic explication for lexical semantic analysis, and cultural script for capturing the cultural norms. The results show that the three core cultural keywords; mugi-mugi, ngasih hormat and adem ayem tentrem provide the cultural norms which express hope or prayer, respect for other entities, and harmony-not contradicting others.Keywords: Ethno-pragmatics, Cultural Keywords, Cultural Discourse